Recognition of candida albicans and role of innate type 17 immunity in oral candidiasis - Pavlova, Anna; Sharafutdinov, Irshad (Microorganisms, 2020)
Candida albicans is an opportunistic pathogenic fungus considered to be a common member of the human microflora. Similar to some other opportunistic microbes, C. albicans can invade and benefit from its host when the immune status of that host is weakened. Most often this happens to immunocompromised individuals, leading to the infection of oral and vaginal mucosae or the systemic spread of the pathogen throughout the entire body. Oropharyngeal candidiasis (OPC) occurs in up to 90 percent of patients with acquired immunodeficiency syndrome (AIDS), making it the most frequent opportunistic infection for this group. Upon first signs of fungal invasion, a range of host signaling activates in order to eliminate the threat. Epithelial and myeloid type cells detect C. albicans mainly through receptor tyrosine kinases and pattern-recognition receptors. This review provides an overview of downstream signaling resulting in an adequate immune response through the activation of various transcription factors. The study discusses recent advances in research of the interleukin-17 (IL-17) producing innate cells, including natural T helper 17 (nTh17) cells, γδ T cells, invariant natural killer T (iNKT) cells and type 3 innate lymphoid cells (ILC3) that are involved in response to oral C. albicans infections.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Candida albicans; IL-17; ILC3; INKT; Innate immunity; Natural Th17 cells; Receptor tyrosine kinase; γδ T cells